ta có: 2010 + 1 > 2010 - 1
\(\Rightarrow A=\frac{20^{10}+1}{20^{10}-1}>1\)
Lại có: 2010 -1 < 2010 - 3
\(\Rightarrow B=\frac{20^{10}-1}{20^{10}-3}< 1\)
=> A > B
ta có: 2010 + 1 > 2010 - 1
\(\Rightarrow A=\frac{20^{10}+1}{20^{10}-1}>1\)
Lại có: 2010 -1 < 2010 - 3
\(\Rightarrow B=\frac{20^{10}-1}{20^{10}-3}< 1\)
=> A > B
So sánh A = 20 10 + 1 20 10 − 1 và B = 20 10 − 1 20 10 − 3
So sánh A = 20 10 + 1 20 10 - 1 v à B = 20 10 + 1 20 10 - 3
So sánh A = 20 10 + 1 20 10 - 1 v à B = 20 10 - 1 20 10 - 3
Cho A = 20 10 + 1 20 10 − 1 và B = 20 10 − 1 20 10 − 3 . So sánh A và B
Cho A = 20 10 + 1 20 10 − 1 ; B = 20 10 − 1 20 10 − 3 . So sánh A và B.
so sánh A và B biết: A=20102010+1/20102011 và B=20102011+1/20102012
So sánh A=20102011+1/20102012+1 và B=20102010+1/20102011+1
So sánh A và B,biết: A = 2010/2011 + 2011/2012 + 2012/2010 và B =1/3 + 1/4 + 1/5 + ...+ 1/17.
Cho A=2010^2011+1/2010^2010+1, B=2010^2012+1/2010^2011
So sánh A và B
Giúp mk nhé mai thi rồi !Cảm ơn
So sánh A và B biết A = 2010/2011+2011/2012+2012/2010 và B = 1/3+1/4+1/5+...+1/17